Profil Angular Cheilitis pada penderita HIV/AIDS di UPIPI RSUD Dr. Soetomo Surabaya 2014 - Alexander Patera Nugraha; Mintarsih Djamhari K; Adiastuti Endah P; Bagus Soebadi; Erwin Asta Triyono; Remita Adya Prasetyo; Sulistyowati Budi (Majalah Kedokteran Gigi Indonesia, 2015)
Profile of Angular Cheilitis in HIV/AIDS Patients at UPIPI RSUD Dr. Soetomo Surabaya 2014. For over twenty years, human immunodeficiency virus (HIV) infection and acquired immunodeficiency syndrome (AIDS) have become a significant public health concern, and the epidemic continues to challenge humanity. HIV related oral lesions can be used as markers of the immune status. Angular Cheilitis (AC) which is one of the seven oral manifestations which are strongly associated with HIV Infection, has been identified and internationally calibrated. The purpose of this research is to identify the Angular Cheilitis and its association with reduced Cluster of Differentiation 4 (CD4+) count in HIV/AIDS patients at Unit Perawatan Intermediet Penyakit Infeksi (UPIPI) RSUD Dr. Soetomo Surabaya. This was an Analytic observasional research with cross-sectional and total sampling method. The samples consisted of 88 HIV/AIDS patients treated in UPIPI RSUD Dr. Soetomo Surabaya from July to August 2014. The Diagnosis of Angular Cheilitis was based on clinical appearance; the oral cavities of the research subjects were examined by dentists specialized in Oral Medicine. CD4+ counts were obtained from the patient’s medical record. Eighty Eight HIV/AIDS patients were examined and there were 120 cases of oral manifestation. There were 31 cases of Angular Cheilitis (25,83%). Angular Cheilitis was found to be significantly correlated to the decrease in CD4+ cell count below 200 cells/mm3 (P< -,245). Risk Relative anaylsis concludes that HIV/AIDS patients with Candidiasis Oral 7.5 more often suffer from AC. There is a correlation between AC and OC (p<0,357). Angular Cheilitis may be used as an alternative to predict CD4+ count at field-based settings to diagnose the immunocompromised status of HIV-infected individuals.